ANALISIS KESALAHAN PENULISAN TEKS EKSPOSISI PROSES SISWA KELAS X SMA SWASTA BINA KASIH KECAMATAN ARAMO - Laia, Fortumen (Universitas Nias Raya, 2025)
Sentence errors make the text not have high limitations, while language errors are characterized by retention of the use of speech forms of various linguistic units which include words. Sentences and paragraphs from systematics and standard Indonesian as well as the use of spelling and punctuation that have been determined in the Indonesian spelling book. This research aims to analyze the Exposition Text Writing Process of Class X students of Bina Kasih Private High School, Aramo District, Academic Year 2023/2024. This type of research is descriptive type qualitative research. This research was conducted in November. Based on the results of the research data analysis, the description of the research data can be concluded that there are 12 data for the thesis and 26 data for arguments as many as the number of students, while in reconfirmation there is 1 (one) data. Based on the results of the research that has been carried out, in terms of the completeness of the text structure, starting from the thesis, arguments and conclusions have appeared in the text. This shows that the students' background knowledge is quite good. Apart from that, the thesis support is organized and logical, in terms of vocabulary and sentence structure, mastery and use of words in sentences are adequate. The use of complex sentence constructions is effective and the meaning is quite clear. The suggestions in this research are (1) The ability to write expository texts needs to be improved further. (2) It is recommended that future researchers continue to pay attention to the development of learning methods used in schools in learning process exposition texts so that students are able to understand all the material presented. (3) Further research needs to be carried out by other researchers in order to provide constructive input for the world of education, especially in improving students' ability to write process exposition texts.